Perancangan Database Sistem Informasi Akuntansi Siklus Penjualan dengan Menggunakan Model REA (Studi Kasus pada PT Yudi Putra, Medan) - Utamy, Ulfah; Evayani, Evayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this reaseach is to design database accounting information system selling cycle by applying the REA model in PT Yudi Putra. The company is located in Medan, North Sumatera which is a company engaged in agricultural exporter. PT Yudi Putra still use manual system of accounting information, it is proper to this company to have a good accounting information system.Data used in this research are primary data in the form of direct interviews with the parties involved in the sales process and secondary data such as documents used by the company in the sales process. The data obtained is used to identify the sales process and implement REA model and then design the database of accounting information systems sales cycle. The results of this study indicate that the accounting information system database design sales cycle by using the REA model has been applied to the PT Yudi Putra so that accounting can be run in real time.Keywords design, database, accounting information system, sales cycle, REA model.